Maxillary second molar with four roots and five canals - Xinjia Sha; Hantang Sun; Jinwu Chen (Elsevier, 2018)
In this case report, we present a maxillary second molar variant, which had two palatal roots with two canals and two buccal roots with three canals, including a second mesiobuccal canal. A 44-year-old female patient complained about a tooth crown fracture and severe pain in her right maxillary second molar. A clinical intraoral inspection and radiography were carried out on the tooth, and a diagnosis of chronic apical periodontitis was made. Four roots (two buccal and two palatal) and five canals (three buccal and two palatal) were found. The anatomical variation of the tooth was further confirmed by cone-beam computed tomography, a cone-fit procedure, and a radiograph with a shifted projection angle. Root-canal treatment was performed under an endodontic microscope.